2017
DOI: 10.1089/neu.2016.4794
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion Guided by Near Infrared Spectroscopy in Neurocritically Ill Patients with Moderate or Severe Anemia: A Randomized, Controlled Trial

Abstract: In neurocritically ill patients (NCPs), the use of hemoglobin level as the sole indicator for red blood cell transfusion (RBCT) can result in under- or over-transfusion. This randomized controlled trial was conducted to ascertain whether a transcranial oxygen saturation (rSO) threshold, as measured by near-infrared spectroscopy, reduces RBCT requirements in anemic NCPs (closed traumatic brain injury, subarachnoid, or intracerebral hemorrhage), compared with a hemoglobin threshold alone. Patients with hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
2
21
3
2
Order By: Relevance
“…Only one small trial ( N = 44) has compared two transfusion targets (100 g/L and 115 g/L) in aSAH, but it was underpowered to examine clinically important outcomes [ 7 ]. Another small mixed brain injury population trial ( N = 102) compared a hemoglobin (Hb) target with a transcranial oxygenation target, but it, too, was underpowered to examine clinically important outcomes [ 8 ]. Despite this absence of evidence, current aSAH management guidelines recommend considering RBC transfusion in anemic patients at risk for cerebral ischemia, but they do not suggest specific transfusion thresholds to guide clinicians [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only one small trial ( N = 44) has compared two transfusion targets (100 g/L and 115 g/L) in aSAH, but it was underpowered to examine clinically important outcomes [ 7 ]. Another small mixed brain injury population trial ( N = 102) compared a hemoglobin (Hb) target with a transcranial oxygenation target, but it, too, was underpowered to examine clinically important outcomes [ 8 ]. Despite this absence of evidence, current aSAH management guidelines recommend considering RBC transfusion in anemic patients at risk for cerebral ischemia, but they do not suggest specific transfusion thresholds to guide clinicians [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional cut-off value for rSO 2 to detect hypoxia is around 60%. In a recent randomised controlled trial in neuro-ICU patients, an rSO 2 value of less than 60% was used to determine RBC transfusion, and less transfusion requirement was noted in this group compared to the haemoglobin-targeted group (Leal-Noval et al, 2017). However, the patient outcomes did not differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown improvement in cerebral oxygenation and metabolic parameters following RBCT, though not the neurologic outcome. [24][25][26][27]…”
Section: Role Of Physiological Triggers In Guiding Red Blood Cell Tramentioning
confidence: 99%
“…48 In a randomized controlled trial conducted on NICU patients, RBCT requirements reduced when RBCT was guided by rSO 2 (< 60%) as against Hb-guided, though the overall outcomes remained the same. 27 Changes in brain tissue oxygenation (PbtO 2 ) were studied following RBCT in TBI patients. 23,24 It was shown that Hb levels < 9 g/dL were associated with PbtO 2 < 20 mm Hg and an unfavorable outcome.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%